The legality of land lease by the state-owned company pt. kai (Persero) - Mirwati, Yulia; Mirwati, Yulia; ., Yakub (International Journal of Engineering and Technology, 2018)
Indonesia Train Company or PT Kereta Api Indonesia (hereafter referred to as PT. KAI (Persero) is a State Owned Campany or Badan Usaha Milik Negara (BUMN), which needs resources to carry out its business. To boost its capital, PT.KAI (Persero) leases its unused land located along the railways that have been closed due to ineffectiveness or the decrease in the operation. This lease carried out over either certified or uncertified land. Although many of the trains in West Sumatra no longer work since independence, PT. KAI (Persero) still leases land. The lease is done in the form of lease quotation document whose format is solely determined by PT.KAI (Persero), similar to a standard contract. In such quotation, the state is leaser and the leaseholder is only obliged to pay for the lease and enjoy / use the land without a balanced agreement. This situation raises the following question: does the arrangement and status of right and lease of land by PT.KAI (Persero) to the public have any legality / legal validity? The study draws on socio-legal data, both primary and secondary obtained through library and field research. The research was conducted in Regional Division II of West Sumatra with land tenants / users of lands that are deemed as assets by PT KAI (Persero). The site was chosen purposively. The results reveal that the leases of PT. KAI (Persero) arein accordance with the provisions of the Ministerial Decree on State-Owned Company along with the Regulation on Railways. However, land leases by PT.KAI (Persero) basedon the Decision Letter from the Ministry of State Owned Company, which is not specifically intended to PT.KAI (Persero), is illigalÂ